Low physiologic oxygen tensions reduce proliferation and differentiation of human multipotent mesenchymal stromal cells - Holzwarth, Christina; Vaegler, Martin; Gieseke, Friederike; Pfister, Stefan; Handgretinger, Rupert; Kerst, Gunter; Müller, Ingo (BMC cell biology, 2010)
Human multipotent mesenchymal stromal cells (MSC) can be isolated from various tissues including bone marrow. Here, MSC participate as bone lining cells in the formation of the hematopoietic stem cell niche. In this compartment, the oxygen tension is low and oxygen partial pressure is estimated to range from 1% to 7%. We analyzed the effect of low oxygen tensions on human MSC cultured with platelet-lysate supplemented media and assessed proliferation, morphology, chromosomal stability, immunophenotype and plasticity.